Stakeholder perceptions of success factors in an academically successful Swazi high school in Manzini, Swaziland - Mabuza, Johannes Tshotsho (Rhodes University, Faculty of Education, Department of Education, 2003)
In contrast with the large number of poorly performing schools in Swaziland over the past decade (1991-2000), a few schools have managed to attain consistently good results. One such school is St Michael's High. This study draws on the perceptions of different major stakeholders at St Michael's of factors deemed to have contributed to academic success at the school. The study thus follows Fertig (2000), who advocates research in effective schools to be done by looking at the perceptions of different stakeholders rather than in relation to an objective checklist. In this study, St Michael's High is found to be an effective school. Its experience can play a vital role in helping other ineffective and failing schools to improve their academic standing and tarnished public image, provided the schools unreservedly commit themselves to changing their ways. This investigation is aimed at understanding the roles which the school leadership and associated stakeholders have played in making St Michael's an exemplary school in Swaziland. Its findings indicate that the schools that themselves take the initiative to improve their effectiveness are the ones which are successful, which accords with the consensus in research literature on school effectiveness. The evidence gathered in this study suggests that St Michael's is characteristic of such effective schools. Since this is a qualitative interpretive case study on perception of success factors in a girls' high school within the city of Manzini, interviews comprising semi-structured questions were highly useful in tapping the understanding of how various stakeholders contribute to the academic achievement of students in the school. The findings, organised in the form of themes, help illuminate what appears to be a systematic and well-focussed approach toward the academic development of the school and the fulfilment of its goals. Every aspect of the school system is thoroughly explored. The validity of the stakeholders' claim that St Michael's High is a dream school for most Swazi children is verified by the school's examination results for the past decade. But what the research reveals are the cultural, academic, social, and moral values and beliefs which serve as a strong anchor for the school leadership and management, and without which St Michael's as an organisation would be unable to meet the challenge of implementing academic and national reconstruction.
Keywords: St Michael's High (Manzini, Swaziland) -- Education -- Swaziland; Education, Secondary -- Swaziland-- Academic achievement -- Swaziland; High school students -- Swaziland; Education -- Parent participation -- Swaziland; Educational leadership -- Swaziland; School management and organization -- Swaziland